Employment needs of young adults with visual disability need to be recognised in Kabul, Afghanistan - Ibrahimkhil, Fahima; Amarkhail, Freba; Sidek, Suriati (Stichting Liliane Fonds, 2021)
Purpose: The aim of this qualitative paper was to understand the employment needs of young adults with visual disability in Kabul, Afghanistan. Method: The phenomenological approach was employed to obtain rich data based on the participants’ personal experiences. In-depth semi-structured interviews were conducted with 14 adults with visual disability, between 20-40 years of age, using open-ended questions to shed light on the employment needs of this population. The data derived from the interviews was transcribed, translated, and thematic analysis was performed. Results: Findings indicate that people with visual disability need to be equipped with essential skills to be competent workers. Support from employers and society is needed and, importantly, encouragement from family members and those involved in advocacy of the people with visual disabilities. Conclusion: Improving the public's awareness regarding personal and vocational abilities of people with visual disabilities, enhancing the skills necessary for employment, promoting their abilities, family support and maintaining positive attitudes are some of the strategies which could result in better employment prospects for people with visual disabilities in Afghanistan.